2017
DOI: 10.1177/1038416217724172
|View full text |Cite
|
Sign up to set email alerts
|

Testing robustness, model fit, and measurement invariance of the Student Engagement Scale in an African university context

Abstract: This study examined a modified version of the Student Engagement Scale, as adopted from the Australasian Survey of Student Engagement. It did so through examining model fit, predictive validity of the engagement factor, and testing of score reliability and measurement invariance across colleges and class years. Participants were volunteer undergraduate students (n = 536) from two colleges of a large university in Ethiopia. Confirmatory factor analysis using structural equation modelling was used. The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These findings lend some empirical support for the results reported in the higher education literature on this field. Research reported comparable extent of engagement behavior and learning outcome but with some variations (Tadesse and Gillies, 2017;Wilson et al, 2015). This implies that not all students experience undergraduate education uniformly.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings lend some empirical support for the results reported in the higher education literature on this field. Research reported comparable extent of engagement behavior and learning outcome but with some variations (Tadesse and Gillies, 2017;Wilson et al, 2015). This implies that not all students experience undergraduate education uniformly.…”
Section: Discussionmentioning
confidence: 96%
“…It consists of a modified questionnaire containing 16 items of student engagement, 13 items of learning gains and two items measuring student satisfaction. These items are part of the results of an extensive validation work as evidenced in the CFA (SEM) study at a large university in Ethiopia (Tadesse and Gillies, 2017;Tadesse et al, 2018;Tadesse et al, 2018a). The researchers measured student engagement based on composite scores using the modified Australasian Survey of Student Engagement (AUSSE) items (Coates, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Some levels of distinctiveness and modifications have been suggested by validation studies of student engagement surveys when used for two years and four year college students [6]. There is also evidence that suggests structural modification for the student engagement scale when used in a single institution study as opposed to large scale study [7][8][9]. Regardless of this, however, in higher education research, development and validation of student engagement and self-reported gains scales and cross-cultural comparisons have been rarely studied [10].…”
Section: Introductionmentioning
confidence: 99%